2010
DOI: 10.4321/s1130-01082010001200009
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary tumor of the pancreas (SPPT): Still an unsolved enigma

Abstract: Solid pseudo-papillary tumor (SPPT) is a rare cystic tumor of the pancreas (1-3% of exocrine tumors of the pancreas) which shows an "enigmatic" behavior on the clinical and molecular pattern. A retrospective analysis of the citological studies and resected specimens of pancreatic cystic tumors from May 1996 to February 2010 was carried out. Three cases of SPPT were found, which are the objective of this study. The diagnosis was established upon occasional finding in the abdominal CT, in spite of sizing between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
15
0
5
Order By: Relevance
“…[8,9,29]. A few studies have suggested a poor prognosis in males; however, larger studies have disputed this association [2,5,7,8,15,16,22,30,31]. Also, the malignant potential of SPN found in children is not significantly different from that in adults [29].…”
Section: Clinical Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9,29]. A few studies have suggested a poor prognosis in males; however, larger studies have disputed this association [2,5,7,8,15,16,22,30,31]. Also, the malignant potential of SPN found in children is not significantly different from that in adults [29].…”
Section: Clinical Managementmentioning
confidence: 99%
“…The predilection for female patients has led to conjectures about the origin of SPN. Some have suggested origin in ovarian tissue deposited in the pancreas during early embryogenesis [5,6]. In the largest meta-analysis to date, 2,744 cases of SPN reported in English language over 50 years (1961-2012) were analyzed, and the results demonstrated an overwhelming majority of female patients (87.8%), with a mean age of 28.5 years at presentation [7].…”
Section: Origin and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-pseudopapillary tumor of pancreas can be visualized in many imaging modalities, such as ultrasonography (US), X-ray computed tomography (CT) and magnetic resonance imaging, which can be used to differentiate it from other pancreatic lesions 1,2,4,[15][16][17][18] .…”
mentioning
confidence: 99%
“…Complete resection is curative in most cases 9,15,19 , but prognostic factors are not well established and clinical evolution cannot be predicted. Rare cases of fatal metastasizing solid-pseudopapillary tumors of pancreas have been previously reported, suggesting that these tumors may occasionally show aggressive clinical behavior 2,9,14,20 . In this article, we present a case of a SPT in a 17-year-old Brazilian woman with a good evolution.…”
mentioning
confidence: 99%